Global trends and current status of distraction osteogenesis: Bibliometric analysis of publications from 1980 to 2021 - Liu, Qi; Liang, Jieyu; Liu, Ze; Guo, Hongbin; Wang, Min; Zhang, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Distraction osteogenesis (DO) has become an important technology for the correction of various congenital and acquired skeletal ridge deformities. It is widely used in oral and maxillofacial surgery, orthopedics, and other disciplines. From 1980 to 2021, the cutting-edge research of DO has been continuously promoted, and the interaction between disciplines has also been deepening. However, the analysis on the global trend and status of DO is relatively rare. Therefore, the aim of our study was to summarize the global trends and current status of DO through bibliometrics. Materials and methods: Web of Science (WOS) core collection database and Medline were used to search DO-related literatures published during 1980–2021. The collected data are imported into Microsoft Excel, Microsoft Word, VOSviewer software for analysis and drawing figure/table. Results: A total of 7,721 publications were included in this study. The United States is the main contributing country to DO (ranking first in terms of total publications, sum of times cited and H-index). Harvard University was the main contributing institution to DO. Journal of Craniofacial Surgery is the main contributing journal of DO related articles. Buchman, SR is the main contributing author to DO related articles. DO related publications can be summarized into 7 clusters: 1) “mechanism study”, 2) “limb bone distraction study”, 3) “alveolar bone distraction study”, 4) “temporomandibular joint ankylosis study”, 5) “maxillofacial surgery study”, 6) “skull distraction study” and 7) “mandible distraction study”. Mandible distraction study has been a hot topic in recent years. In addition, the “management”, “osteogenesis” and “reconstruction” of DO have been the research hotspots from 1980 to 2021. Conclusion: From 1980 to 2021, the total number of DO articles has increased rapidly and maintained a steady trend. The United States is the predominant country in the field. Surgery, dental, and oral surgery and orthopaedics are hot fields of DO research. The study of mandible distraction has been paid more and more attention and will become a hotspot in the future. Our study is beneficial for scientists to specify the research hotspot and development direction of DO.